Pengaruh Ukuran Perusahaan dan Risiko Kredit terhadap Stabilitas Keuangan Bank di Indonesia Periode 2019-2023 - Muhammad Ridho Akmal; Muhammad Iqbal Pribadi; Rahman Anshari (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of company size and credit risk on bank financial stability in Indonesia during 2019-2023. This study used a quantitative approach with panel data regression and a sample of 235 bank-observations from 25 commercial banks and 24 regional development banks. The Fixed Effect Model (FEM) and Generalized Least Squares (GLS) methods were used to address autocorrelation problems. The results show that both company size (SIZE) and credit risk (NPL) have a significant and negative influence on bank financial stability (Zscore). In other words, greater bank size and higher credit risk contribute to a decline in financial stability. The study concludes that bank management should be more cautious and selective in extending credit and growing their operations in order to maintain financial stability.